Should fines also benefit victims? An evaluation of fines as a form of punishment in Malaysia with special reference to Islamic law - Hussin, Nasimah; Zawawi, Majdah; Wan Muhammad, Ramizah (International Islamic University Malaysia, 2017)
Existing financial punishments in Malaysia, usually in the form of fines for certain offences are payable to the government. The victims (if any) are not entitled to benefit from such payment, which implies that the system has failed to compensate the victims for losses that they have suffered. Another issue is the option provided for some offenders to pay a fine in lieu of imprisonment. This negates the principle of justice as it allows the rich to pay whilst the poor will have to face imprisonment. The question arises concerns the effectiveness of imposing fines to remedy the ailments in society. It also questions the reformative value of the punishment and how it can benefit the victim. This article evaluates the existing legal framework relating to financial punishments in Malaysia. In doing this, the objective of the article is to provide suggestions as to how these questions could be answered by incorporating Shari’ah principle of al-’adl